Socioanálise de pré-noções no discurso jornalístico sobre educação - Gilson R. de M. Pereira; Maria da Conceição L. de Andrade (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
The text analyses articles published in two major weekly magazines with a large national circulation and aims at investigating the proportion of those pre-notions disclosed by media professionals in the production and broadcasting of information and points-of-view on education. In view of the position held by the media in the general economy of symbolic goods, we start from the hypothesis according to which the educational practices of teachers and other social agents are shaped by a given social construction of reality, that is, by principles and views of education imposed, generally in a subtle fashion, by journalists and the general social space.